Analysing water provision in the critical interface of formal and informal urban water regimes. Issue 2 (17th February 2023) - Karpouzoglou, Timos; Vij, S.; Blomkvist, P.; Juma, B.; Narain, V.; Nilsson, D.; Sitoki, L.
ABSTRACT: Science and technology studies and urban political ecology have made important contributions to the understanding of water provision in the Global South. In this article we develop insights from these fields with the aim to understand the blurring boundaries of urban water regimes and their power relations mediated by actors, institutions and technology. Furthermore, we explore how urban water regimes can form a critical interface which is a form of institutional–actor space where formal and informal water regimes encounter each other through conflict and cooperation.